In silico analyses of human collagen protein function prediction - Ahmed, MS; Kamruzzaman, M; Rana, MM; Akond, Z; Mollah, MNH (Journal of Bio-Science, 2018)
Collagen is the extracellular matrix protein in the several connective tissues in the human body. It is an important component for mediating cell-cell interactions and pathological conditions in human body. In this study we perform the analysis of physiochemical properties and investigate the functional characteristics of human collagen proteins. Also investigate the functional protein groups by the statistical analysis. The collagen protein family consisting 28 members in human which are involving in the complex structure of protein. The protein function, protein sequence properties, domain composition, phylogenetic and protein-protein interaction (PPI) networks analysis of human collagen alpha-1 protein sequences are implemented by the online bioinformatics tools which are currently available. Based on the PCA analysis amino acid composition, features of collagen protein sequences are divided into two supreme influential functional groups such as collagen 12, 14, 20 formed one group and the rest of others formed another group. The protein-protein interaction network study using STRING showed that top interacting score of functional group proteins 0.952, 0.939 and 0.929. The most common functional domain of collagen proteins are VWC, C4, LamG, VWA, KU, C1Q, TSPN and FN3. Physicochemical, functional and phylogenetic classification can give extensive information of protein’s structure and function. The depiction of alpha-1 chains of collagen protein family in human collagen 12, 14 and 20 as a prospective protein cluster. These three proteins are possess, low glycine and proline, very high aliphatic index and a close evolutionary relation in the human skin. J. bio-sci. 24: 55-65, 2016